The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/dneu.20941
|View full text |Cite
|
Sign up to set email alerts
|

Induction of axon growth arrest without growth cone collapse through the N‐terminal region of four‐transmembrane glycoprotein M6a

Abstract: During development, axons elongate vigorously, carefully controlling their speed, to connect with their targets. In general, rapid axon growth is correlated with active growth cones driven by dynamic actin filaments. For example, when the actin-driven tip is collapsed by repulsive guidance molecules, axon growth is severely impaired. In this study, we report that axon growth can be suppressed, without destroying the actin-based structure or motility of the growth cones, when antibodies bind to the four-transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 62 publications
2
30
1
Order By: Relevance
“…Furthermore, in the previous study, we found notable axon behavior involving M6a; when anti-M6a antibody binds to M6a protein in culture, the axons stalls the elongation (Sato et al, 2011a). Interestingly, during this reaction, the axons maintain the actin-rich growth cones exhibiting highly motile movement.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Furthermore, in the previous study, we found notable axon behavior involving M6a; when anti-M6a antibody binds to M6a protein in culture, the axons stalls the elongation (Sato et al, 2011a). Interestingly, during this reaction, the axons maintain the actin-rich growth cones exhibiting highly motile movement.…”
Section: Introductionmentioning
confidence: 67%
“…For analysis of expression of M6 proteins, ICR wild-type mice were purchased from Japan SLC, Inc. M6a knockout mice in the C57BL/6 background were produced previously (Sato et al, 2011a), and maintained in the animal facility at the National Institute of Genetics. Drs.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations